"Coloured", You're on Your Own? A Dialectic Between Biko's Black Consciousness Thought and the Post-Apartheid Conditions of the "Coloured" People in South Africa. Issue 2 (4th May 2022) - Baron, Eugene
ABSTRACT: There is still long way to go in terms of reconciliation and social cohesion, especially against the background of the recent resurgence of ethnic and racial overtones in South Africa. The author engages this phenomenon and the manifestation through a conversation with the Black consciousness thought of Steve Biko, but particular his statement: "Black man, you're on your own!" The author uses this statement as part of Biko's Black consciousness thought to function in this paper as a theoretical framework to reflect on how South Africans and the post-apartheid government should espouse (not only celebrate) the ideology of Steve Biko in policy and practice. The author engages the experiences of the "Coloured" people in South Africa as a case study for what it would mean to embrace Biko's thought in policy and practice in the quest for social cohesion in the post-apartheid context.